Relationship Of Ball Muscle Power Towards Spike Volyball Skills - Delfi Marzah; Feby Elra Perdima (Perkumpulan Dosen Muda Bengkulu, 2020)
This study aims to determine the correlation between leg muscle power to volleyball spike skills in class X SMA Negeri 1 Ulu Musi, Empat Lawang. The method used is a descriptive correlational method, because basically this study aims to determine the relationship between variables. The research data collection instrument was carried out by measuring the power of the leg muscles using the Vertical Jump test, then the Spike skill was performed with the Spike. The results of data analysis indicate that the hypothesis proposed is acceptable, there is a positive relationship between the two variables, namely of 0.977 is positive, meaning that the greater the score obtained, the stronger the relationship between the two variables. The test for the significance of the correlation coefficient was carried out by means of the value r count with r table at α = 5% with N = 24 obtained r table of 0.404 because the correlation coefficient between rx.y = 0.97 r (0.5) (24) = 0.404 means the correlation between the power of leg muscles on the Spike skills of SMA Negeri 1 Ulu Musi students is significant. Thus, the hypothesis which says